The Role of Neighborhood and Community in Building Developmental Assets for Children and Youth: A National Study of Social Norms Among American Adults - Scales, Peter C.; Benson, Peter L.; Roehlkepartain, Eugene C.; Hintz, Nicole R.; Sullivan, Theresa K.; Mannes, Marc (Psykhe, 2004)
Unrelated adults play potentially important roles in the positive socialization of children and youth, but studies of adolescents suggest the majority of adults do not engage positively with young people on an intentional, frequent, and deep basis. As a result, only a minority of young people report experiencing key developmental assets that have been associated with reduced risk-taking behaviors and increased thriving. Social norms theory suggests that adults will be more likely to get deeply involved with young people outside their family if that involvement is viewed as highly important, and if they perceive a social expectation to do so. A nationally representative sample of 1,425 U.S. adults was surveyed to determine the degree of importance American adults ascribed to 19 positive asset-building actions, and the degree to which the adults they knew actually engaged with young people outside their own families in those positive ways. The results showed that only a minority of Americans experience consistent normative motivation for engaging with other peoples children. There is a large gap between what adults consider important and what they actually do to construct positive, intentional relationships with children and youth. Community stability and extent of communitybuilding activities in which adults engage, including participation in religious services, volunteering, and neighborhood meetings, are associated with differences among adults in the degree of normative motivation for engaging with young people. In addition to these group differences, however, there also are nine asset-building actions two functioning as genuine social norms and seven as social values that great majorities of American adults consider highly important. The foundation therefore exists in public opinion to make explicit greater permission for adults to become more deeply engaged in the lives of children outside their families and to thereby define new normative expectations for all adults to share in being responsible for the well-being of young people. © 2001 John Wiley & Sons, Inc.